Leaf tissue specific transcriptome sequence and de novo assembly datasets of Asiatic mangrove Rhizophora mucronata Lam. - S.P. Meera (Data in Brief, 2020)
Transcriptome data is beneficial to explore molecular mechanisms of extreme adaptations in non- model organisms like mangroves. In this data article, five major datasets and two data sub sets of a salt secreting mangrove, Rhizophora mucronata Lam. were described. A combination of Illumina HiSeq 2500, Trinity, BLAST X, Bowtie 2 and BLAST 2GO was used for RNA Seq, de novo assembly, transcript annotation, gene expression estimation and gene ontology annotation respectively. The RNA Sequence (Read 1 and Read 2) in Sequence Read Archive amounting to 46,366,348 paired end raw reads is the first data set made open for de novo or comparative transcript assembly. Assembled sequences of 93960 gene transcripts constitute the second data set in Transcriptome Shotgun Assembly. The gene/protein annotations to the assembled transcripts give two sub data sets containing 93960 each of GenBank and GenPept entries with comprehensive cDNA and translated protein sequences of genes. Of these, predicted proteins for 87768 coding sequences, mapped to UniProtKB serve as the third data set. The gene expression levels of the annotated transcripts comprise the fourth data set in Gene Expression Omnibus. The fifth data set in Figshare includes 44,028 gene ontology terms extracted for 21,073 confident transcripts. The data sets provide a valuable resource for further analyses including transcriptomic changes in response to environmental stresses.